NILAI-NILAI PENDIDIKAN DALAM SENI KALIGRAFI ARAB KARYA BAMBAMG PRIYADI - Rachmad Arif Ma’ruf; Anwar Sa’dullah; Khoirul Asfiyak (VICRATINA, 2020)
Arabic calligraphy is one of the beautiful arts writing in Islamic culture which is one of the medium that covers all fields of science, both religious, social, economic, cultural and historical. The form of written by Bambang Priyadi refers to the writing style of Imam Hasyim Muhammad Al-Baghdadi and Imam Syauqi. In addition, his calligraphy works were also influenced by spiritual factors, education, the form of Arabic calligraphy and the environment. In Arabic calligraphic art by Bambang Priyadi There are also educational values, namely the value of social education, the value of religious education, and the value of moral education. This research aims to describe the values of education in Arabic calligraphic art by Bambang Priyadi. To achieve that goal, the approach used in this research is a qualitative, descriptive research. The procedure of collecting data is done using an interview method which is a method of collecting data using a verbal question-and-answer path with research source, and method of documentation, which is to find data on things or variables in the form of records, books, gallery and so on. Based on the results of the study, it can be concluded that the educational values contained in the Arabic calligraphic art by Bambang Priyadi, the value of social education, the value of religious education, and the value of moral education.